Mandibular Mass as an Only Presentation of Metatatic Renal Cell Carcinoma For Four Years: A Case Report - Gooran, Shahram; Fakhr Yasseri, Alimohammad; Behtash, Negar; karimi, Arash; Khalili, Masoud; Asadi, Mahboobeh (Urology Journal, 2017)
Renal cell carcinoma is one of the most common tumors of the urinary tract. This tumor may appear as Para neoplasticsyndromes or distant metastasis. Metastases in uncommon areas are one of the characteristics of renal tumors.One of the uncommon metastatic renal masses areas is the mandible. In different studies, patient survival aftermetastasis diagnosis is usually one year or less. In this study we introduce a patient with mass of the right mandiblewhich existed four years before his referral, and in examinations it was diagnosed as metastasis with renal origin.